PRELIMINARY HEARINGS IN THE CRIMINAL PROCEDURE OF THE REPUBLIC OF ARMENIA: IMPORTANCE, CHALLENGES, AND PROSPECTS FOR REFORM - Hovhannisyan, Lusine (State and Law, 2025)
Criminal justice encompasses a multifaceted system of procedures aimed at safeguarding individual rights, maintaining procedural standards, and upholding justice. The introduction of preliminary hearings into Armenian criminal procedure marks a significant transformation in the legal landscape. These recent legislative changes are designed to streamline judicial processes, enhance the efficiency of case management, and promote fairness and transparency in court proceedings. By incorporating preliminary hearings, the Armenian legal system seeks to reduce delays and procedural bottlenecks, ensuring that cases progress more swiftly while upholding the principles of justice. This shift reflects a broader commitment to reform and the modernization of criminal justice practices to align with international standards. Overall, the preliminary hearing mechanism stands as a testament to Armenia’s dedication to reinforcing its legal framework and fostering trust in the judiciary through improved procedural integrity and equitable outcomes.